Static and Fatigue Strength Assessment of Composite Patch Repair - Paboeuf, Stéphane; Deydier, Maxime; Sourisseau, Quentin; Lepretre, Emilie; Chataigner, Sylvain; Chapeleau, Xavier (Volume 3: Materials Technology; Subsea Technology, 2024)
International audience Marine and Offshore industries are looking for rapid, efficient and qualified repair solutions for damaged or corroded structures. Patch made in composite materials can offer such qualities as confirmed by the Joint Industry Project StrengthBond Offshore (JIP SBO) led by Bureau Veritas. Indeed, since 2019, Bureau Veritas, in collaboration with its partners, studied and analyzed the strength behaviour of composite patch repairs based on a large numerical and experimental testing campaign. The JIP SBO consortium designed a layered composite patch composed of an epoxy resin with glass and carbon fibres, and proposed an installation procedure. Small-scale and large-scale specimens were tested in static and fatigue, and numerical simulations were done in order to develop a robust methodology for the strength assessment of composite patch repairs. This paper first presents the comparison of two patch designs, one with a long scarf at the ends of the bonded composite patch, and the other one with a short scarf. In addition, two manufacturing processes, infusion and hand lay-up, are compared for long scarf specimens. The static resistance of the two patch designs and manufacturing processes is determined by tensile and bending tests. The results show that long scarf specimens have a higher resistance and that the manufacturing process has little influence. Finally, fatigue tests on long scarf specimens, and for the two studied manufacturing processes, are detailed and compared with a FPSO (Floating Production Storage Offloading) histogram.